Embodied Islamic Character Education through Performing Arts: A Phenomenological Study of Panggung Gembira - Amanda Najla Krisnandya Armansyah; Syarifah Syarifah; Muwahidah Nurhasanah; Nuraeni Rahmawati (Al-Qalam Institue, 2025)
This study explores the role of Panggung Gembira as a medium of embodied Islamic character education at Pondok Modern. The research aims to analyze how performing arts activities contribute to the formation of Islamic character among sixth-grade female students through lived educational experiences. Employing a qualitative phenomenological approach, the study collected data through in-depth interviews, participant observation, and documentation. The participants consisted of sixth-grade female students involved in organizing and performing Panggung Gembira. Data were analyzed using Interpretative Phenomenological Analysis to identify themes emerging from students’ experiences during the preparation and performance processes. The findings reveal that Panggung Gembira functions not merely as an artistic performance, but as an embodied educational arena integrating cooperation, conflict management, creativity, self-management, self-evaluation, leadership, and independence within the pesantren culture. Islamic values were internalized through collective artistic practices, emotional engagement, organizational responsibility, and reflective interaction. The study further demonstrates that performing arts in pesantren serve as a hidden curriculum through which students experience moral and spiritual formation beyond formal classroom instruction. This research contributes to contemporary Islamic education discourse by positioning performing arts as a transformative pedagogical space for embodied religiosity, female leadership development, and experiential character education in modern pesantren.